Transcriptome and Oxylipin Profiling Joint Analysis Reveals Opposite Roles of 9-Oxylipins and Jasmonic Acid in Maize Resistance to Gibberella Stalk Rot - Wang, Qing; Sun, Yali; Wang, Fang; Huang, Pei-Cheng; Wang, Yinying; Ruan, Xinsen; Ma, Liang; Li, Xin; Kolomiets, Michael V.; Gao, Xiquan (Frontiers in Plant Science, 2021)
Gibberella stalk rot (GSR) caused by Fusarium graminearumis one of the devastating diseases of maize causing significant yield losses worldwide. The molecular mechanisms regulating defense against this pathogen remain poorly understood. Recently, jasmonic acid, a major oxylipin hormone produced by 13-lipoxygenases(LOX), has been associated with maize susceptibility to GSR. However, the specific roles of numerous 9-LOX-derived oxylipins in defense against GSR remain unexplained. In this study, we show that disruption of a 9-LOX gene, ZmLOX5, resulted in increased susceptibility to GSR, indicating its role in defense. To understand how ZmLOX5 regulates GSR resistance, we conducted transcriptome and oxylipin profiling using a zmlox5-3 mutant and near-isogenic wild type B73, upon infection with F. graminearum. The results showed that JA biosynthetic pathway genes were highly up-regulated, whereas multiple 9-LOX pathway genes were down-regulated in the infected zmlox5-3 mutant. Furthermore, oxylipin profiling of the mutant uncovered significantly higher contents of several jasmonates, but relatively lower levels of 9-oxylipins in zmlox5-3 upon infection. By contrast, B73 and a more resistant inbred line, W438, displayed relatively lower levels of JAs, but a considerable increase of 9-oxylipins. Taken together, these results suggest antagonistic interaction between 9-oxylipins and JAs, where 9-oxylipins contribute to resistance, while JAs facilitate susceptibility to F. graminearum.